2022
DOI: 10.3389/fgene.2022.860161
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD8+ T Cell Related Biomarkers in Ovarian Cancer

Abstract: Background: Immunotherapy is a promising strategy for ovarian cancer (OC), and this study aims to identify biomarkers related to CD8+ T cell infiltration to further discover the potential therapeutic target.Methods: Three datasets with OC transcriptomic data were downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases. Two immunotherapy treated cohorts were obtained from the Single Cell Portal and Mariathasan’s study. The infiltration fraction of immune cells was quantified u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
5
4
1
Order By: Relevance
“…Likewise, the existence of CD8 + T lymphocytes and B lymphocytes in TIME has been associated with better predictive outcomes in ovarian cancer. Our discoveries conform with these prior findings, implying that USP30-AS1 could have significant predictive consequences in ovarian cancer [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the existence of CD8 + T lymphocytes and B lymphocytes in TIME has been associated with better predictive outcomes in ovarian cancer. Our discoveries conform with these prior findings, implying that USP30-AS1 could have significant predictive consequences in ovarian cancer [39,40].…”
Section: Discussionsupporting
confidence: 91%
“…CD38 could serve as a biomarker for re ecting prognosis and survival. Some previous research [14,31] and our study demonstrated the protective effect of high CD38 expression in improving the survival of EOC patients. Possible correlation with immune cell in ltration and signaling pathways have also been investigated, the CD38 high group exhibited increased in ltration of NK cells [32], γδT cells [33] with tumorkilling ability and immune regulation, as well as DC [34] that induce CD8 + T cell-mediated immune response [31,35].…”
Section: Discussionsupporting
confidence: 66%
“…Some previous research [14,31] and our study demonstrated the protective effect of high CD38 expression in improving the survival of EOC patients. Possible correlation with immune cell in ltration and signaling pathways have also been investigated, the CD38 high group exhibited increased in ltration of NK cells [32], γδT cells [33] with tumorkilling ability and immune regulation, as well as DC [34] that induce CD8 + T cell-mediated immune response [31,35]. The differences observed between the CD38 high and CD38 low groups primarily involve signaling pathways regulating cell proliferation, growth, differentiation, apoptosis, and tumor metabolism.…”
Section: Discussionsupporting
confidence: 66%
“…Li et al used weighted gene co-expression network analysis (WGCNA) and nonnegative matrix factorization (NMF) method sample classification to identify key biomarkers in CD8 T cell-related genes and construct prognostic features in OVCA. 12 Chen et al explored the underlying mechanisms of the tumorigenesis and progression based on genes associated with OVCA clinical features. 13 Considering the advantages of bioinformatics analysis recognizing markers in various tumors, in this study, according to the previous literature, 8,14,15 10 m1A genes were collected to cluster OVCA patients into two tumor subtypes to excavate pivotal m1A-related biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al used weighted gene co‐expression network analysis (WGCNA) and nonnegative matrix factorization (NMF) method sample classification to identify key biomarkers in CD8 T cell‐related genes and construct prognostic features in OVCA 12 . Chen et al explored the underlying mechanisms of the tumorigenesis and progression based on genes associated with OVCA clinical features 13 .…”
Section: Introductionmentioning
confidence: 99%